Assessment of glyphosate and its metabolites’ residue concentrations in cultured African Catfish offered for sale in selected markets in Ibadan, Oyo State, Nigeria - Alarape, Selim Adewale; Fagbohun, Adekemi Florence; Ipadeola, Oladeni Adegoke; Adeigbo, Anthony Ayodeji; Adesola, Ridwan Olamilekan; Adeyemo, Olanike Kudirat (Frontiers in Toxicology, 2023)
Glyphosate is a non-targeted organophosphate insecticide whose solubility and mobility in hydrophilic solvents enable its rapid leaching into the soil and subsequent contamination of ground and surface water and possible build-up in the aquatic food chain microbial buildup in plant tissues and contamination of groundwater. Looking atBased on the public health importance of glyphosate to in fish through consumption, it is crucial to understand determine the currentits residue concentration in local culture Clarias gariepinusfish species. The aim of the present study is to evaluate glyphosate's residue concentrations and its metabolites in cultured African Catfish offered for sale in selected markets in Ibadan. A total of twenty-five (25) adult Clarias gariepinus (300 ± 50g) were sourced from five (5) selected active fish markets (Ojoo, Iwo road, Eleyele, Challenge, and Apata) within the Ibadan metropolis. and transported to the Fish and Wildlife Unit Laboratory, at the